LANGKAH STRATEGIS MANAJEMEN DALAM MENGHADAPI PENGGUNAAN SITUS SOSIAL MEDIA OLEH KARYAWAN PADA JAM KERJA - Bruri Trya Sartana (Universitas Budi Luhur, 2011)
Some institutions in Indonesia has banned the use of social networking systems at the office either by enacting legislation or blocking network access. Social networking system has encouraged the use of technology far beyond office systems have been developed. Utilization of electronic communications concepts such as knowledge exchange, groupware, collaboration and so forth have been used effectively and efficiently on systems of social networks in the form of group communication facilities of friends, ideas and developing ideas together. Based on the above, companies need to adapt and develop strategies that take into accountthe risks and benefits of the use of social media sites in office hours. Keywords : social media, social networking systems